2014
DOI: 10.1530/eje-13-0729
|View full text |Cite
|
Sign up to set email alerts
|

Association between GH receptor polymorphism (exon 3 deletion), serum IGF1, semen quality, and reproductive hormone levels in 838 healthy young men

Abstract: Introduction: GH activity may be involved in male reproductive function. A common genetic polymorphism in the gene encoding the GH receptor (GHR) results in deletion of the entire exon 3 sequence (GHRd3 isoform). The short GHRd3/d3 isoform seems more sensitive compared with full-length receptors (GHRfl/fl). Aim: To investigate the associations between GH activity, evaluated by exon 3 GHR polymorphism, and serum IGF1 vs reproductive hormones, semen quality, and pre-and postnatal growth in healthy young males (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…In contrast, GH does not appear to enhance gametogenesis in many GH-replete animals, since GH supplementation does not alter germ cell apoptosis in bulls [ 91 ] nor sperm number in monkeys [ 63 ] and postpubertal rats [ 92 ]. Moreover, men with the GHR3d (3rd exon) deletion do not have improved semen quality or steroid production, despite the increased GH sensitivity conveyed by this mutation [ 93 ].…”
Section: Male Fertilitymentioning
confidence: 99%
“…In contrast, GH does not appear to enhance gametogenesis in many GH-replete animals, since GH supplementation does not alter germ cell apoptosis in bulls [ 91 ] nor sperm number in monkeys [ 63 ] and postpubertal rats [ 92 ]. Moreover, men with the GHR3d (3rd exon) deletion do not have improved semen quality or steroid production, despite the increased GH sensitivity conveyed by this mutation [ 93 ].…”
Section: Male Fertilitymentioning
confidence: 99%
“…Its serum levels are known to augment with the increase of TV in healthy children (27). Several previous studies have tried to understand if rhGH treatment may somehow improve sperm parameters in adulthood (28)(29)(30) or whether a relationship between IGF1 serum levels in adulthood and sperm parameters do exist (31). The results of these studies showed no effect, and, therefore, the idea that the GH-IGF1 may play a role in the reproductive system was abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 However, regardless of the large number of studies reporting the effect of the GHRd3 polymorphism on human growth under some conditions, the direct effect of the GHRd3 polymorphism on the final adult height in the general population remains to be investigated. The sensitive GHRd3 allele may also be associated with increased male reproductive function such as high semen quality and sex-hormones levels 10 and a decreased risk of breast cancer. 11 The GHRd3 polymorphism has also been implicated in the pathogenesis of insulin resistance and type-2 diabetes mellites (T2DM).…”
Section: Introductionmentioning
confidence: 99%